Effect of adding fermented cabbage waste extract to starter feed pellets on the performance of pre-weaning FH calves - Mukodiningsih, Sri; Achmadi, Joelal; Wahyono, Fajar; Erlina, Siti (Journal of Advanced Veterinary Research, 2026)
Starter feed accelerates reticulo-rumen development in pre-weaning calves, but proper care is crucial to reduce the risk of diarrhea. This study aimed to evaluate the effect of adding fermented cabbage waste extract (FCWE) to starter feed on calf performance. The experimental design used was a completely randomized design, with 4 treatments (T0: SF without FCWE; T1: SF + 2% FCWE; T2: SF +4% FCWE and T3: SF +6% FCWE) and 5 replications. The materials used were 20 pre-weaned FH calves (initial body weight 39 + 4,35 kg), yellow corn ground, soybean meal, rice bran, molasses, mineral mix, cabbage waste, sugar and salt. Feeding trial was done 8 weeks. Starter feed is given twice a day after milk is given, while forage and water are given ad libitum. The parameters measured were dry matter intake (DMI), average daily gain (ADG), rumen VFA and NH3. The data DMI and ADG were analyzed with ANOVA and Duncan’s test, while rumen VFA and NH3 were analyzed with descriptive analysis. The result indicated that there was no significant effect of treatment on dry matter intake, but there was significant effect (P<0.05) of those on average daily gain. Rumen VFA-NH3 is in accordance with standards. In conclusions, starter feed with 6% FCWE improves pre-weaning calf performance and is recommended as the best formula.